2016
DOI: 10.1163/18759866-08502005
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, functional morphology, evolutionary ecology and systematics of the invasive gastropod Cipangopaludina japonica (Viviparidae: Bellamyinae)

Abstract: The anatomy, functional morphology and evolutionary ecology of the Viviparidae, and the subfamily Bellamyinae in particular, are incompletely known. Partly as a result, genealogical relationships within the family remain poorly understood. Because of this lack in knowledge, few informed hypotheses exist on ancestral states, how differences in body plans between the subfamilies evolved, and how the peculiar biogeographic distribution patterns of viviparids have arisen. Here we document the anatomy, morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The basic anatomical structure of the digestive system of the Egyptian thiarid snail Mieniplotia scabra conforms to that of any other style bearing snails (Graham, 1939;Moustafa (1987); Strong & Glaubrecht , (2003); Vogler et al , (2014); Bocxlaer and Strong (2016); Khalil & Aly (1997). It consists mainly of the mouth, which leads to the pgayngeal cavity (StarmÜhlner, 1969), the muscular buccal mass, the esophagus, the stomach, the style sac, the intestine, the rectum which ends with the anal papilla and the glandular structures which are the digestive and salivary glands.…”
Section: Discussionsupporting
confidence: 57%
“…The basic anatomical structure of the digestive system of the Egyptian thiarid snail Mieniplotia scabra conforms to that of any other style bearing snails (Graham, 1939;Moustafa (1987); Strong & Glaubrecht , (2003); Vogler et al , (2014); Bocxlaer and Strong (2016); Khalil & Aly (1997). It consists mainly of the mouth, which leads to the pgayngeal cavity (StarmÜhlner, 1969), the muscular buccal mass, the esophagus, the stomach, the style sac, the intestine, the rectum which ends with the anal papilla and the glandular structures which are the digestive and salivary glands.…”
Section: Discussionsupporting
confidence: 57%
“…): as juveniles(Van Bocxlaer & Strong, 2016) 20-43/4.5-6.5 mm: as embryos (this study) Ussuripaludina 5-70/4.5-8.0 mm: as embryos (this study)A3Margarya 6-8/5 whorls: as embryos (indicated as C. dianchiensis in Lu et al, 2014) 2-8/exceeding 10 mm: as juveniles(Zhang et al, 2015) …”
mentioning
confidence: 62%
“…Campeloma decisum and Ci. japonica occupy similar habitats and ecological niches: individuals are frequently found on soft sediments in rivers and lakes, and both species are presumed to filter feed from the water column as well as ingest organic material present in the substrate (Allison 1942;Chamberlain 1958;Bocxlaer and Strong 2016).…”
Section: Introductionmentioning
confidence: 99%